Serum Free Zinc Is Associated With Vaccination Response to SARS-CoV-2 - Chillon, Thilo Samson; Maares, Maria; Demircan, Kamil; Hackler, Julian; Sun, Qian; Heller, Raban A.; Diegmann, Joachim; Bachmann, Manuel; Moghaddam, Arash; Haase, Hajo; Schomburg, Lutz (Frontiers in Immunology, 2022)
Background Zinc (Zn) is an essential trace element with high relevance for the immune system, and its deficiency is associated with elevated infection risk and severe disease course. The association of Zn status with the immune response to SARS-CoV-2 vaccination is unknown. Methods A cohort of adult health care workers (n=126) received two doses of BNT162B2, and provided up to four serum samples over a time course of 6 months. Total SARS-CoV-2 IgG and neutralizing antibody potency was determined, along with total as well as free Zn concentrations. Results The SARS-CoV-2 antibodies showed the expected rise in response to vaccination, and decreased toward the last sampling point, with highest levels measured three weeks after the second dose. Total serum Zn concentrations were relatively stable over time, and showed no significant association with SARS-CoV-2 antibodies. Baseline total serum Zn concentration and supplemental intake of Zn were both unrelated to the antibody response to SARS-CoV-2 vaccination. Time resolved analysis of free Zn indicated a similar dynamic as the humoral response. A positive correlation was observed between free Zn concentrations and both the induced antibodies and neutralizing antibody potency. Conclusion While the biomarkers of Zn status and supplemental Zn intake appeared unrelated to the humoral immune response to SARS-CoV-2 vaccination, the observed correlation of free Zn to the induced antibodies indicates a diagnostic value of this novel biomarker for the immune system.